Cadmium‐tolerant bacteria: current trends and applications in agriculture. (1st March 2022) - Bravo, D.; Braissant, O.
Abstract: Cadmium (Cd) is considered a toxic heavy metal; nevertheless, its toxicity fluctuates for different organisms. Cadmium‐tolerant bacteria (CdtB) are diverse and non‐phylogenetically related. Because of their ecological importance these bacteria become particularly relevant when pollution occurs and where human health is impacted. The aim of this review is to show the significance, culturable diversity, metabolic detoxification mechanisms of CdtB and their current uses in several bioremediation processes applied to agricultural soils. Further discussion addressed the technological devices and the possible advantages of genetically modified CdtB for diagnostic purposes in the future.